Ekologi lingkungan dalam al-Qur’an dan Hadits - Syarafina, Ainassabih Liwani (Maliki Interdisciplinary Journal, 2023)
The problems associated with the environment are numerous and widespread. Environmental problems have existed since humans lived on the face of the earth. Human life cannot be separated from the environment, humans are social beings that require a balance between themselves personally, others, and with their environment. Islam encourages its people to always protect the environment and preserve nature. Along with the development of the human age, biological sciences have also experienced developments that gave birth to several cabaang, including zoology, botany, microbiology and ecology. Ecology etymologically is a science that studies the mutual relationship between living things and their environment. Islam encourages its people to always protect the environment and preserve nature because everything that humans do to their environment will have an impact on them. In the Qur’an surah Al A’raf verse 56 Allah forbids man to do damage, whether at sea, on land, in the air and even anywhere.